2016
DOI: 10.1038/nplants.2015.218
|View full text |Cite
|
Sign up to set email alerts
|

Specific control of Arabidopsis BAK1/SERK4-regulated cell death by protein glycosylation

Abstract: Precise control of cell death is essential for the survival of all organisms. Arabidopsis thaliana BRASSINOSTEROID INSENSITIVE 1-associated receptor kinase 1 (BAK1) and somatic embryogenesis receptor kinase 4 (SERK4) redundantly and negatively regulate cell death through elusive mechanisms. By deploying a genetic screen for suppressors of cell death triggered by virus-induced gene silencing of BAK1/SERK4 on Arabidopsis knockout collections, we identified STT3a, a protein involved in N-glycosylation modificatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
83
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 80 publications
(87 citation statements)
references
References 50 publications
1
83
0
3
Order By: Relevance
“…As has been reported previously, silencing Arabidopsis Col-0 plants with VIGS constructs containing GFP does not affect Pst growth ( Fig. 2D; de Oliveira et al, 2016). Silencing of CRK22 and CRK28 in the crk29-1 knockout resulted in significantly higher bacterial titers compared with Col-0 control plants 3 d post inoculation (Fig.…”
Section: Genetic Analyses Of Crk-mediated Defensesupporting
confidence: 61%
See 3 more Smart Citations
“…As has been reported previously, silencing Arabidopsis Col-0 plants with VIGS constructs containing GFP does not affect Pst growth ( Fig. 2D; de Oliveira et al, 2016). Silencing of CRK22 and CRK28 in the crk29-1 knockout resulted in significantly higher bacterial titers compared with Col-0 control plants 3 d post inoculation (Fig.…”
Section: Genetic Analyses Of Crk-mediated Defensesupporting
confidence: 61%
“…We have demonstrated that CRK28 is both glycosylated and phosphorylated in planta. Recently, CRK4 was demonstrated to be glycosylated, and STAUROSPORIN AND TEMPERATURE SENSITIVE3 N-glycosylation was required for CRK4-induced cell death and protein accumulation in Arabidopsis (de Oliveira et al, 2016). Glycosylation also has been shown to be important for the function of multiple immune receptors, including FLS2, EFR, and Cf proteins (van der Hoorn et al, 2005;Nekrasov et al, 2009;Saijo et al, 2009;Häweker et al, 2010;Liebrand et al, 2012).…”
Section: Some Of the Largest Gene Families In Plants Encodementioning
confidence: 99%
See 2 more Smart Citations
“…The very similar phenotype of both double 360 mutants confirms this observation, explaining the bak1 bir3 double mutant phenotype 361 as a cell death response caused by the absence of BAK1 and BKK1 (He et al,362 transcript levels were not altered in the bir3 mutant compared to wild type 364 (Supplemental Figure 19 A, B). Yamada et al (2016) reported that depletion of BAK1 365 primes PEPR-mediated cell death responses, and de Oliveira et al (2016) suggested 366 that cysteine-rich receptor kinases (CRK) might be client proteins of protein 367 glycosylation involved in BAK1-regulated cell death. Therefore, sensitizing pro-death 368…”
Section: Botrytis-induced Kinase1 (Bik1) Which In Turn Phosphorylatementioning
confidence: 99%